A Paper-Based Analytical Device Integrated with Smartphone: Fluorescent and Colorimetric Dual-Mode Detection of β-Glucosidase Activity - Wei-Yi Zhang; Tao Tian; Li-Jing Peng; Hang-Yu Zhou; Hao Zhang; Hua Chen; Feng-Qing Yang (Biosensors, 2022)
In this work, indoxyl-glucoside was used as the substrate to develop a cost-effective, paper-based analytical device for the fluorescent and colorimetric dual-mode detection of β-glucosidase activity through a smartphone. The β-glucosidase can hydrolyze the colorless substrate indoxyl-glucoside to release indoxyl, which will be self-oxidized to generate green products in the presence of oxygen. Meanwhile, the green products emit bright blue-green fluorescence under ultraviolet–visible light irradiation at 365 nm. Fluorescent or colorimetric images were obtained by a smartphone, and the red-green-blue channels were analyzed by the Adobe Photoshop to quantify the β-glucosidase activity. Under the optimum conditions, the relative fluorescent and colorimetric signals have a good linear relationship with the activity of β-glucosidase, in the range of 0.01–1.00 U/mL and 0.25–5.00 U/mL, and the limits of detection are 0.005 U/mL and 0.0668 U/mL, respectively. The activities of β-glucosidase in a crude almond sample measured by the fluorescent and colorimetric methods were 23.62 ± 0.53 U/mL and 23.86 ± 0.25 U/mL, respectively. In addition, the spiked recoveries of normal human serum and crude almond samples were between 87.5% and 118.0%. In short, the paper-based device, combined with a smartphone, can provide a simple, environmentally friendly, and low-cost method for the fluorescent and colorimetric dual-mode detection of β-glucosidase activity.